2007
DOI: 10.1016/j.ejheart.2007.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Plasma level of cardiotrophin‐1 as a prognostic predictor in patients with chronic heart failure

Abstract: Background: Cardiotrophin-1 (CT-1) is a member of the interleukin (IL-6) family of cytokines and is increased in patients with chronic heart failure (CHF). Aims: To evaluate the prognostic role of CT-1 in patients with CHF. Methods and results: We measured the plasma levels of CT-1, brain natriuretic peptide (BNP), and IL-6 in 125 patients with CHF. Patients were monitored for a mean follow-up period of 2.9 years. Plasma levels of CT-1 increased with severity of CHF. There was a significant negative correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 20 publications
(30 reference statements)
2
35
1
1
Order By: Relevance
“…The hazard ratio for mortality in patients with plasma BNP > 170 pg/mL and CT-1>658 fmol/mL was 2.48 compared to those with plasma BNP>170 pg/mL and CT-1<658 fmol/mL. These fi ndings indicate that plasma CT-1 measurement provides additional prognostic information and that combined levels of CT-1 and BNP are more accurate at predicting mortality in patients with CHF than either marker alone 114 .…”
Section: Prognosis Of Chfsupporting
confidence: 51%
“…The hazard ratio for mortality in patients with plasma BNP > 170 pg/mL and CT-1>658 fmol/mL was 2.48 compared to those with plasma BNP>170 pg/mL and CT-1<658 fmol/mL. These fi ndings indicate that plasma CT-1 measurement provides additional prognostic information and that combined levels of CT-1 and BNP are more accurate at predicting mortality in patients with CHF than either marker alone 114 .…”
Section: Prognosis Of Chfsupporting
confidence: 51%
“…Two experimental studies revealed the importance of CT-1 in the pathogenesis of atrial myocardial fibrosis and developing arrhythmias over the release of high concentrations of calcium during diastole [16,17]. There are evidence that CT-1 plasma levels can be elevated in patients with hypertension [20], coronary artery disease [21,22], and heart failure [23]. A recent experimental study indicated that CT-1 accelerates the development of atherosclerotic lesions by stimulating the inflammasome, foam cell formation associated with CD36 and acyl-CoA: cholesterol acyltransferase-1 upregulation in macrophages, and migration, proliferation, and collagen-1 production in vascular smooth muscle cells [24].…”
Section: Discussionmentioning
confidence: 99%
“…CT-1 was also proposed as a prognostic biomarker for death and heart failure in patients with acute myocardial infarction [29] as well as increased levels of CT-1 were reported to be associated with fibrosis, remodeling and depression of myocardial contractility in patients with heart failure [23]. We think that inflammation leads structural and electrical remodeling that consequently induces AF relapse and investigation of this vicious circle may provide pivotal information for the prevention of AF.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, serum levels of upstream activators of STAT3, in particular the interleukin IL-6 cytokines, such as leukemia inhibitory factor (LIF), and cardiotrophin (CT)-1 are elevated in patients with cardiac insufficiency and serve as a strong independent predictor for the morbidity and mortality in patients with chronic heart failure after myocardial infarction [132][133][134]. Additionally, serum levels of the soluble form of the gp130 receptor (sgp130), the common receptor subunit of all IL-6 cytokines, appear to correlate with the severity of left ventricular dysfunction in addition to already established prognostic markers such as B-type natriuretic peptides [135,136].…”
Section: Stat3 and Anthracycline-induced Cardiotoxicitymentioning
confidence: 99%